Pengaruh Viral Marketing, Product Quality dan Taste of Burger King terhadap Purchase Decision Konsumen Burger King di Kota Bandung - Azriel Muhamad Sani; Akbar Rohandi, Mochamad Malik (UNISBA Press, 2024)
Abstract, Such rapid growth in the fast food industry can be felt in the city of Bandung. This can be seen from the large number of fast food restaurants found. So, there needs to be an appropriate strategy so that consumers decide to purchase the products being sold. Fast food restaurants can use digital marketing methods by using viral marketing on social media platforms.Apart from that, fast food restaurants also need to maintain and improve product quality and taste in the food and beverage products they sell and make them unique compared to competitors' products. This research aims to analyze